Lapatinib, trastuzumab or the combination added to neoadjuvant chemotherapy for breast cancer - Liang, Quan; Fu, Qiang; Li, Wei; You, Jiacong; Zhao, Zhanchao (Bangladesh Journal of Pharmacology, 2016)
The aim of this study was to compare the efficacy and safety of trastuzumab versus the combination of trastuzumab and lapatinib added to neoadjuvant chemotherapy for HER2 positive breast cancer. PubMed, MEDLINE, The Cochrane Library, Web of Science and nearly 5 years of the important international conference on oncology records were searched for randomized clinical trials that compared lapatinib plus trastuzumab and neoadjuvant chemotherapy (NAC) with trastuzumab in combination with NAC and that included pathologic complete response rate as the primary outcome. Finally, 6 clinical randomized controlled trials were included. Meta-analysis shows that pathological complete response rate was significantly increased in trastu-zumab plus lapatinib group than single use trastuzumab group (53.4%, 40.4%, RR = 1.75, 95% CI 1.38 2.23, p<0.001). In conclusion, the combination of trastuzumab and lapatinib added to neoadjuvant chemotherapy in HER2 positive breast cancer is more effective.